Individual characterization of Iberian pig through NIRS technology: Implementation in Sierra de Sevilla, S.A. - Serrano A.; De Pedro E.; Morera C.; Vázquez P.; Moreno A.; Garrido-Varo A.; Guerrero J.E.; Pérez Marín D.C.; Fernández-Cabanás V.M.; García-Olmo J.; Núñez-Sánchez N. (7th International Symposium on the Mediterranean Pig, 2012)
The Iberian pig industry has established several quality control programs in order to determine and guarantee the pig feeding system, especially in the last period of growing. These programs consisted of on-farm Iberian pig inspection or fatty acids composition of subcutaneous tissue fat. The potential of NIRS technology in the classification of Iberian pig carcasses in the several commercial categories, according to their feeding system, has been reported by researchers at the University of Cordoba in the last years. However, the implementation of this technology at industrial level has not been yet as widespread as expected in comparison with other industries such as animal feed industry. This communication reports the results obtained in the first year of the project for the implementation of NIRS technology as quality control tool in the “Sierra de Sevilla” Company which elaborates meat products from Iberian pig. The use of NIRS technology as quality control tool allowed a fast, reliable and inexpensive characterization of each animal. Individual characterization is of great importance in “recebo” batches, where a large variability between animals was found. The good results obtained to date have given individual information of its animals to the Company providing a better quality control of their products and also monitoring the farm suppliers.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)